ESP Students’ Perception Towards the Use of ICT in English Learning - Fatnalaila; Ciptaningrum, Dyah Setyowati (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aimed to explore ESP students’ perceptions towards the use of Information and Communication Technology (ICT) in English learning. Data obtained was analyzed by employing the descriptive analysis techniques using questionnaire distributed to 50 students from the Economic Faculty of Yogyakarta State University in the form of Google form. The questionnaire adapted from Davis (1989) Technology Acceptance Model (TAM). The study revealed that a significant majority of students perceive ICT as beneficial tool in improving their performance in ESP course, with 77% recognizing its usefulness and 79% agreeing on its ease of use. Additionally, 76.5% of students demonstrated positive attitudes toward ICT use, while 81% expressed a strong intention to continue using it in their learning. These findings highlight the importance of ICT in fostering language skills relevant to students’ academic and professional goals